Labor Markets and Social Policy in Central and Eastern Europe : The Accession and Beyond - Barr, Nicholas (Washington, DC: World Bank, 2012)
This book summarizes social policy reform during the transition and European Union accession and analyses the social policy challenges which continue to face both old and new member states. Specifically, the book amplifies two sets of arguments. First, social policy under communism was in important respects well-suited to the old order and - precisely for that reason - was systematically badly-suited to a market economy. Strategic reform directions thus followed from the nature of the transition process and from constraints imposed by EU accession. Secondly, successful accession is not the end of the story: economic and social trends over the past 50 years are creating strains for social policy which all countries - old and new members - will have to face.